PENGARUH TAX PLANNING, INTELLECTUAL CAPITAL, DEBT POLICY, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2020 - 2024) - Witaningsih Witaningsih; Martini Martini (CV. Denasya Smart Publisher, 2026)
This study aims to determine the effect of tax planning, intellectual capital, debt policy, and profitability in company value. This study was conducted on Infrastructure Sector Companies listed on the Indonesia Stock Exchange for the period 2020-2024. The sampling method useid in this study was purposive sampling, and 39 infrastructure sector companies were obtained. The data analysis techniques used in this study was multiple linear regression using SPSS software version 22. Based on the results of study, it can bei concluded that tax planning has no effect on company value, intellectual capital has a positive and significant effect on company value, debt policy has no effect on company value, profitability has a negative and significant effect on company value.